Climate Change Shapes the Dengue Landscape: A Narrative Review - Ahmad, Nouman; Ahmad, Hamdan (Pena Medika : Jurnal Kesehatan, 2024)
Introduction: Climate change is a critical driver of vector-borne diseases, notably dengue. Rising global temperatures, altered precipitation patterns, and increased extreme weather events enhance Aedes mosquitoes' habitats, the primary vectors of dengue. The pathogenesis of dengue, driven by any of the four serotypes of the dengue virus (DENV-1 to DENV-4), is exacerbated by climate-induced changes that support mosquito breeding and survival. Methods: This review analyzes selective studies from the last decade, integrating epidemiological data and climate models to explore the impacts of climatic variables on dengue dynamics. Adaptation strategies, including vaccination, vector control, and community-based interventions, were evaluated for their effectiveness in mitigating dengue transmission Results: Epidemiological data indicate approximately 390 million annual infections globally, with rapid urbanization and inadequate vector control compounding the issue. Climate models highlight significant increases in dengue incidence and shifts in its geographic distribution, particularly in regions such as the Americas, Asia, and potentially Europe. Promising adaptation strategies, such as the Communication for Behavioral Impact (COMBI) plan and constrained optimization models, have demonstrated efficacy in enhancing dengue prevention and control. Discussion: As climate change continues to alter ecosystems, integrating climatic data into public health strategies is essential for adaptive responses. Comprehensive and region-specific approaches, robust public health infrastructures, and international cooperation are paramount to address the rising threat of dengue. A need for international cooperation and robust public health infrastructure is necessary to address the multifaceted challenges posed by climate change on dengue transmission